Drinking Ethanol Has Few Acute Effects on CYP2C9, CYP2C19, NAT2, and P‐Glycoprotein Activities but Somewhat Inhibits CYP1A2, CYP2D6, and Intestinal CYP3A: So What?. Issue 6 (10th May 2018) - Gazzaz, Malaz; Kinzig, Martina; Schaeffeler, Elke; Jübner, Martin; Hsin, Chih‐hsuan; Li, Xia; Taubert, Max; Trueck, Christina; Iltgen‐Breburda, Juliane; Kraus, Daria; Queckenberg, Christian; Stoffel, Marc; et al.
Abstract : We quantified the effect of acute ethanol exposure (initial blood concentrations 0.7 g/L) on major drug metabolizing enzymes and p‐glycoprotein. Sixteen healthy Caucasians participated in a randomized crossover study with repeated administration of either vodka or water. Enzyme/transporter activity was assessed by a cocktail of probe substrates, including caffeine (CYP1A2/NAT2), tolbutamide (CYP2C9), omeprazole (CYP2C19), dextromethorphan (CYP2D6), midazolam (CYP3A), and digoxin (P‐glycoprotein). The ratio of AUC0‐t of dextromethorphan for ethanol/water coadministration was 1.95 (90% confidence interval (CI) 1.48–2.58). The effect was strongest in individuals with a CYP2D6 genotype predicting high activity ( n = 7, ratio 2.66, 90% CI 1.65–4.27). Ethanol increased caffeine AUC0‐t 1.38‐fold (90% CI 1.25–1.52) and reduced intestinal midazolam extraction 0.77‐fold (90% CI 0.69–0.86). The other probe drugs were not affected by ethanol. The results suggest that acute ethanol intake typically has no clinically important effect on the enzymes/transporters tested.